Peculiarities of psychosocial stress in relative of cerebrovascular pathology patients - Yavorskaya, T. P. (Journal of Education, Health and Sport, 2018)
A disease is stressful situation both for the patient and for his family. Materials and methods. On the grounds of PIC at the base of Emergency Medicine Centre of Kharkiv Regional Clinical Hospital during 2016-2018, 252 relatives of cerebrovascular pathology patients were examined. The patients had different stages of the diseases. The psychosocial stress was assessed according to L. Reeder’s “Psychosocial Stress Scale”. To analyze the potential stressor factors, each group was subdivided according to Boston Stress Test for stress-resistance. Results. The appearance of clinical symptoms of somatic illness in a patient was accompanied by an increasing rate of psychosocial stress among family members (1.44±0.63 points in the relatives of patients without disease; 1.51±0.67 points in relatives of cardiovascular risk patients; 1.67±0.65 points in the relatives of transitory ischemic attacks patients and 2.0±0.47 points in the relatives of stroke patients, p < 0.05). The components of psychosocial stress were the destabilization of interpersonal communication against the background of manifestations and consequences of the disease, reducing the patient’s work capacity and respectively the growing need for physical and emotional support, redistribution of family’s roles and responsibilities, and the exhaustion of family resources (psychological, social, physical). It was revealed that increasing stress risk is accompanied by an increasing level of psychosocial stress among family members and jointly creates a psychopathogenetic basis for the development of family maladaptation in CVD patient’s family. Conclusions. Medico-psychological measures directed at the families of cerebrovascular pathology patients are an important component of complex help.